Educators’ Dexterity in Test Construction within Senior High Schools: Implications for Educational Administrators - Oghenerume, Rioborue Alexander (Universitas Majalengka, 2025)
Educators’ dexterity in constructing effectual, dependable, and valid tests is indispensable for accurately measuring learners’ outcomes and supporting data-driven decisions by educational administrators. This exploration probed educators’ test construction dexterity across all disciplines in senior high schools within Edo South Senatorial District, tackling two foremost lacunas in existing explorations: the focus on all disciplines and the implications for educational administrators. Applying survey design and census sampling, data were amassed from 1,596 educators across 129 public senior high schools via the validated Educators’ Dexterity in Test Construction Questionnaire (EDTCQ), with a dependability coefficient of 0.91. The discoveries divulged generally low test construction dexterity, with significant discrepancies based on sex and experience. Male educators and those with more experience demonstrated superior dexterity levels, while no significant discrepancy was discovered based on qualification. These latest discoveries underscored the need for targeted professional development, mentorship, and sex-based training to boost educators’ assessment dexterity.